Participation of citizens in pre-trial hearings - Brink, Barbara (Mednarodna revija za javno upravo, 2014)
In 2011 the Dutch Central Appeals Tribunal, the highest Dutch court of appeal in legal areas pertaining to social security and the civil service, started consulting the parties of a dispute at an early stage in the procedure, in order to include them in the decisions about the procedural steps to be taken in the settlement of the appeal. One of the underlying rationales is that the involvement of the parties will lead to more acceptance of and contentment with the result. Since the acceptance of court decisions is considered as a criterion for the quality of the procedure, this approach should result in a better quality of the case treatment. In this article the initial results of this new case treatment are presented in the light of expectations from the literature on citizen participation in policy processes of public agencies. The data indicate that the New Case Management Procedure at the Central Appeals Tribunal can lead to an improvement of the quality of the case treatment, by inviting citizens to discuss with the judge about the case treatment. However, the procedure itself does not guarantee this increased quality.
Keywords: administrative law procedures; Dutch Central Appeals Tribunal; new case management; Nizozemska; novi javni management; Osrednji pritožbeni tribunal; postopki upravnega prava; reševanje sporov